2023
DOI: 10.1021/acsami.3c05477
|View full text |Cite
|
Sign up to set email alerts
|

Disregarded Free Chains Affect Bacterial Adhesion on Cross-Linked Polydimethylsiloxane Surfaces

Abstract: The surface properties exhibited by chemically cross-linked polydimethylsiloxanes (CPDMS) such as morphology, stiffness, and wettability have garnered great interest in the study of bacteria–material interactions. Nevertheless, the hidden factor of uncross-linked free PDMS chains that dissociate in CPDMS has often been overlooked when studying the biofilm formation on these polymeric elastomer surfaces. Here, we undertake a comparative characterization of the effects of free chains in CPDMS on bacterial adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…As calculated via eq , the uncrosslinked oligomer content in the unextracted gels was ∼46, 33, 11, and 1% for the ultrasoft, soft, standard, and stiff gels (Figure and Table ). While the ultrasoft is being examined for the first time by our group, our findings align with previous studies, where the ethanol and hexane extraction processes determined the oligomer content to be 24 and 38% for soft gels (40:1), 8 and 3% for standard gels (10:1), and 5 and 3% for stiff gels (5:1).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…As calculated via eq , the uncrosslinked oligomer content in the unextracted gels was ∼46, 33, 11, and 1% for the ultrasoft, soft, standard, and stiff gels (Figure and Table ). While the ultrasoft is being examined for the first time by our group, our findings align with previous studies, where the ethanol and hexane extraction processes determined the oligomer content to be 24 and 38% for soft gels (40:1), 8 and 3% for standard gels (10:1), and 5 and 3% for stiff gels (5:1).…”
Section: Resultssupporting
confidence: 89%
“…These manuscripts all report different findings, possibly due to the different bacteria and microbiology analysis techniques used. Sun et al used a plate-counting process that removed bacterial cells from the PDMS with a saline solution prior to a serial dilution and redepositing the cells onto an agar plate for growth overnight. In contrast, we used fluorescence microscopy, which, after a light rinse to remove loosely adhered bacteria, immediately imaged and quantified the bacteria grown directly on the PDMS gels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these values were in good accordance with previous studies, as elastic moduli for fouling release coatings are typically ranged between 0.2 and 9 MPa [3,[23][24][25]. In their recent study, similar results were observed by Sun et al [26]. They observed that when the crosslinking density of the polymeric network of PDMS decreases, Young's Coatings 2024, 14, 149 9 of 15 consequently decreases from 8.90 to 2.99 MPa.…”
Section: Surface Properties Of Pdms Coatingssupporting
confidence: 90%